Post-cycling Interface Strength Test of Geogrids - Garcia, Gian Franco Napa; Lodi, Paulo César [UNESP] (Springer Nature, 2020)
Geosynthetic-reinforced soil structures are commonly used in seismic design in regions. The performance of GRES under seismic conditions can be found to range from very good to catastrophic. This paper presents the implementation of a test to evaluate the influence of pre-cycling on the post-cycling resistance of a soil–geogrid system. Tests were performed on a PVE uniaxial geogrid with a tensile strength of 400 kN/m and a clean sand with 89% compaction and friction angle of 37.5°. The system was subjected to cyclic pullout tests at 40 and 80% of the monotonic strength. After the pre-cycling, a posterior monotonic pullout test was performed to evaluate the influence of the previous cycling on the final post-cycling strength. A test protocol was established to apply 50, 100, 500 and 5000 cycles with 40% and 80% pullout resistance amplitudes. At the 40% amplitude, the system exhibited stable increasing behavior in terms of resistance and cyclic displacement. Failure was not reached during the pre-cycling stage at 40% amplitude. At the 80% amplitude, the system failed at 250 cycles, and cyclic displacement was found to be erratic for all pre-cycling cases. The results suggest a general tendency of the pre-cycling to increase the post-cycling resistance. However, a combination of high cyclic amplitude with large number of cycles may lead to failure. Exposure to seismic events could be considered in the design of GRES though a rationally chosen reduction factor is applied.
Keywords: Geogrid; Geosynthetics; Post-cycling strength; Pre-cycling; Pullout